A bibliometric analysis of Sukūk Waqf - Mahadi, Nur Farhah; Yusuf, Muhammad-Bashir Owolabi (IIUM Institute of Islamic Banking and Finance, 2025)
This study presents a comprehensive bibliometric analysis of the research on ṣukūk waqf, an innovative financial instrument that combines the principles of ṣukūk (Islamic bonds) and waqf (Islamic endowment). The objective of this research is to explore the current state of academic literature, identify emerging trends, and uncover potential avenues for future investigations in this domain. The study employed bibliometric techniques to systematically review relevant publications indexed in prominent databases, such as Scopus and Web of Science, from the inception of the concept to the present day. Bibliometric indicators, including publication trends, citation analysis, co-authorship patterns, and thematic mapping, were utilized to gain insights into the intellectual structure and evolution of the ṣukūk waqf research landscape. The findings reveal a growing interest in ṣukūk waqf, with a steady increase in the number of publications over the past decade. The analysis highlights the geographical concentration of research, with prominent contributions from Malaysia and Indonesia, indicating the regional significance of this financial innovation. The study also identifies key thematic clusters, such as the design and structuring of ṣukūk waqf instruments, their applications in socioeconomic development, and the challenges associated with their implementation. The bibliometric analysis provides a comprehensive overview of the current state of ṣukūk waqf research, facilitating the identification of knowledge gaps and emerging research opportunities. The study’s findings can inform scholars, policymakers, and practitioners in their efforts to further explore and leverage the potential of ṣukūk waqf for sustainable and socially responsible finance.